Adherence Level to Antihypertensive Medication Among Internal Medicine Outpatients at Anna Medika General Hospital Madura - Wulandari, Tri Wahyuni (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Hypertension is one of the chronic diseases known as a “silent killer” because it often presents without symptoms but can lead to serious complications such as stroke, kidney failure, and even death. The main challenge in hypertension treatment is patient non-adherence to regularly taking medication as prescribed, which can reduce treatment effectiveness and increase the risk of complications. A high level of adherence is essential to achieve optimal therapeutic outcomes and prevent harmful long-term effects. This study aims to determine the level of adherence to antihypertensive medication among patients at the internal medicine outpatient clinic of Anna Medika General Hospital Madura. The research used a descriptive quantitative method with a survey approach, employing the 8-item Morisky Medication Adherence Scale (MMAS-8) as the data collection instrument. The questionnaire was distributed to 96 respondents who met the inclusion criteria. Data were analyzed using the Guttman scale, and statistical processing was performed using SPSS version 16.0. The results showed that all respondents fell into the adherent category, with an average adherence rate of 94%. This indicates that most patients are aware of the importance of taking medication regularly, even while traveling or feeling well. The study concludes that the level of adherence to antihypertensive medication at Anna Medika General Hospital is high, serving as a positive indicator for the long-term effectiveness of therapy.